Math, asked by StarTbia, 1 year ago

Simplify :
(–1 2/11) + (–3 5/11) + (6 3/11)

Answers

Answered by Anonymous
4
Bonjour!

 =  > ( - 1 \frac{2}{11} ) + ( - 3 \frac{5}{11} ) + (6 \frac{3}{11} ) \\  \\  =  >  -  \frac{13}{11}   -  \frac{38}{11}  +  \frac{69}{11}  \\  \\  =  >  \frac{ - 13 - 38 + 69}{11}  \\  \\  =  >  \frac{18}{11}

Hope this helps...:)
Answered by Rishab143
3

 =  - 1 \frac{2}{11}   - 3  \frac{5}{11}  + 6 \frac{3}{11}  \\  \\  =  \frac{ - 13}{11}  -  \frac{38}{11}  +  \frac{69}{11}  \\  \\  =  \frac{ - 13 - 38 + 69}{11}  \\  \\  =  \frac{18}{11}  \\  \\  = 1 \frac{7}{11}
Similar questions